La diversidad de los paisajes vegetales de fruticultura en El Bierzo: la pujanza de los regadíos de manzanos y peras y la conservación de “los sotos” de castaños = The diversity of the landscape of the fruit crops in El Bierzo, the strength of the irrigation of apple and pear trees and the preservation of the "sotos" of chestnuts trees - San Román Rodríguez, José María (Polígonos. Revista de Geografía, 2012)
Las condiciones climáticas de la fosa tectónica de El Bierzo favorecen los cultivos leñosos, especialmente la fruticultura. Este paisaje agrario se moderniza e intensifica en los años 1960 con la construcción de dos canales de regadío. La fruticultura de pepita, manzanos y perales, la de hueso con los cerezos y la de frutos secos, con las castañas concen-tra las principales producciones. Un paisaje en el que los productos agrícolas con marcas de calidad pera conferencia, manzana reineta y castañas concentran las principales producciones. Este paisaje ha sido muy valorado por los autores bercianos, como Gil y Carrasco. The climatic conditions in the tectonic depression of El Bierzo are favourable to tree-growing, especially the cultivation of fruit-trees. This agricultural landscape was modernized and cultivation intensified in the 1960s when two irrigation canals were constructed. The growing of pomaceous fruits, such as apples and pears, of drupes or stone fruits, such as cherries, and of nuts, such as chestnuts, comprises the principal products. Such crops dominate a landscapeThe climatic conditions in the tectonic depression of El Bierzo are favourable to tree-growing, especially the cultivation of fruit-trees. This agricultural landscape was modernized and cultivation intensified in the 1960s when two irrigation canals were constructed. The growing of pomaceous fruits, such as apples and pears, of drupes or stone fruits, such as cherries, and of nuts, such as chestnuts, comprises the principal products. Such crops dominate a landscape in which most agricultural produce is of items with a quality mark, particularly Conference pears, Reinette apples and chestnuts. The scenery of this area has been greatly praised in literary works, such as those of the nineteenth-century novelist Gil y Carrasco in which most agricultural produce is of items with a quality mark, particularly Conference pears, Reinette apples and chestnuts. The scenery of this area has been greatly praised in literary works, such as those of the nineteenth-century novelist Gil y Carrasco.